Is it really worthwhile revising the same fl ora repeatedly? A case study in Thai Orchidaceae - Pedersen, Henrik Æ. (Thai Forest Bulletin (Botany), 2014)
For many purposes, scientifi c Floras (dealing with one, several or all plant families on a national or regional scale) are the most intensively used surveys and identifi cation tools for species of vascular plants. Flora of Thailand will be the fi rst real standard Flora to cover all families of fl owering plants in Thailand. Nevertheless, the Thai representatives of a number of plant groups have undergone one or more revisions previously. Is it worthwhile revising such groups again for Flora of Thailand – and would it even make sense to start thinking of a second edition? To throw some light on this, I compared three successive revisions of the orchid subfamily Orchidoideae in Thailand (published in 1958–1964, 1977–1978 and 2011, respectively). The series of revisions exhibited a progressive increase in the net number of accepted taxa. The relative increase was highest from the fi rst to the second revision, but still substantial from the second to the third. The net results obscured an even higher number of changes (additions end exclusions of taxa) that partly neutralized each other – and other changes were in themselves neutral in relation to the net number of taxa accepted. Classifi cation at species level, but not at genus level, tended to stabilize over time. Altogether, the results demonstrate that both the second and the third revision were worthwhile indeed, as each of them provided comprehensive changes (arguably improvements) compared to the latest previous revision.